Disaffected Coattail Effect: The Election Anomaly in Local Political Party in Aceh, Indonesia - Fadhli, Fadhli (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
This research explains how the Aceh Party, which supported Prabowo-Gibran in the 2024 presidential election, not only won the election in Aceh but also managed to secure more seats in the local parliament. This vote gain seemed anomalous when other supporting parties saw the negative coattail effect of the national political contestation. Aceh, a region synonymous with political Islam, became a vote bank for the Anies-Muhaimin candidate pair, who were associated with Islamism. As a result, the party supporting them secured a significant vote share in the Aceh legislative elections. The coattail effect also affected the parties supporting the other unpopular candidate pairs, Prabowo-Gibran and Ganjar-Mahfud, which experienced a decrease in the number of votes in the legislative elections. Diverting from the patterns, the Aceh Party supported Prabowo-Gibran yet managed to secure more seats in the parliament. It was the only political party supporting an unpopular candidate yet secured more seats in the parliament. This article analyses the factors that boosted the Aceh Party's votes in the 2024 elections. Based on the literature study, this article shows that the Aceh Party's victory was inseparable from the campaign strategy shift in local political contestation. Despite supporting unpopular candidates, the Aceh Party was able to translate ideology into a demarcation between national political interests in Jakarta and regional political interests in Aceh. The emphasis on cultural and local political identity has strengthened the Aceh Party's political base.